2007
DOI: 10.1038/sj.bjc.6603899
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy for fatigued cancer survivors: long-term follow-up

Abstract: An earlier randomised-controlled trial demonstrated the positive effects of cognitive behaviour therapy (CBT), especially designed for fatigued cancer survivors in reducing fatigue, functional impairments and psychological distress. In the current prospective study, we were able to examine the long-term effect of CBT in patients who completed the therapy. Predictors of fatigue severity at follow-up were exploratory investigated. Sixty-eight patients who completed CBT were assessed at pretreatment, post-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 30 publications
3
99
1
8
Order By: Relevance
“…A cutoff score Ն35 indicates severe fatigue [24]. It has been used in previous research investigating fatigue in cancer survivors and has shown sensitivity to detect change [3,22,27,28].…”
Section: Instrumentsmentioning
confidence: 99%
“…A cutoff score Ն35 indicates severe fatigue [24]. It has been used in previous research investigating fatigue in cancer survivors and has shown sensitivity to detect change [3,22,27,28].…”
Section: Instrumentsmentioning
confidence: 99%
“…From a previous influenza study in cancer patients with similar sample size and using identical measurement techniques, we know that our group sizes are sufficient to detect significant differences in immunological parameters. 34 Fatigue severity was determined according to the CIS-fatigue.…”
Section: Participantsmentioning
confidence: 99%
“…Nitekim kanser hastalarında gözüken psikiyatrik bozukluklara ve hastalık gruplarına özgü farklı BDT programları geliştirilmiştir. [16,28] BDT programlarının amacı kanserin tanısı, evresi ve hastada görülen psikolojik yakınmaya göre değişiklik gösterir. Ayrıca BDT yeni tanı alan ve erken evre döneminde olan hastalarda kanserle ilgili belirtileri ve tedavinin neden olduğu yan etkileri azaltmak için geliştirilmişken terminal dönem kanser hastalarında anksiyeteyi azaltmak için başa çıkma stratejilerini öğretmek ve endişeleri azaltmaya yardımcı olmak için geliştirilmiş-tir.…”
Section: Bdt'nin Hedefleriunclassified
“…Çok sayıda psikoterapi yönteminin içerisinde BDT'nin kanser hastalarında yaşam kalitesinin yükseltilmesi, sıkıntının azalmasında, psikolojik ve fiziksel belirtileri hafifletmekte en etkili tedavi yöntemlerinden birisi olduğu yapılan birçok çalışmada belirtilmiştir. [16,17] Kısa vadeli ve uygulanabilmesinin kolay oluşu, hastaların öz yeterliliğini artırması ve kanser hastalarında gözüken farklı psikolojik sıkıntıları üzerinde etkinliği nedeniyle BDT kanser hastalarında çok sık kullanılır. [18] Son zamanlarda ülkemizde kanser hastalarında görülen psikiyatrik bozukluklar üze-rinde birçok çalışma yapılmış olmasına rağmen bu hastalıkların tedavi yöntemlerinden biri olan özellikle BDT'nin uygulanması, içeriği ve kanser hastalarında görülen psikiyatrik bozukluklar üzerindeki etkinliği konusunda yazılan derleme çalışmasına rastlanmamıştır.…”
unclassified